Rapid-burning and rapid-heating material for thermal battery, preparation method of rapid-burning and rapid-heating material and prepared thermal battery

By using bimetallic nano-energy-containing thin film material as the heating material of thermal battery, the problems of slow combustion speed and large gas production of existing materials are solved, and the activation time of thermal battery and the improvement of electrochemical performance are achieved.

CN119549522APending Publication Date: 2025-03-04CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411652925.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing thermal battery heating materials are slow to burn or produce large gases when burning, resulting in long activation time and poor load capacity, which cannot meet the high-performance electrical energy needs in modern warfare.

Method used

Bimetal nano-energy-containing thin film materials are prepared by alternate stacking of Al and metal foils such as Ni, Ti, Nb, Cu, etc., and nano-energy-containing thin film materials are formed by annealing, ultrasonic cleaning, hot pressing and rolling.

Benefits of technology

It significantly improves the heat transfer rate of the positive electrode material of the thermal battery, shortens the activation time, reduces the internal resistance during the operation of the thermal battery, and improves the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549522A_ABST
    Figure CN119549522A_ABST
Patent Text Reader

Abstract

The invention discloses a fast-burning and fast-heating material for a thermal battery, a preparation method thereof and the prepared thermal battery, the fast-burning and fast-heating material is formed by alternately rolling two metal foils together, one metal is Al, the other metal is one of Ni, Ti, Nb and Cu, and the thickness of a bimetallic nano energetic film material is 0.1-0.5 mm. The bimetallic nano energetic film material can generate a violent exothermic reaction under the stimulation of lower energy, and has the characteristics of high reaction speed, large heat release, no gas generation, metal alloy serving as a reaction product and the like. When the material is used as a thermal battery heating material, the battery activation time can be effectively shortened, and the internal resistance of the thermal battery in the working process is reduced, so that the electrochemical performance of the thermal battery is comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal batteries, and in particular relates to a fast-burning and fast-heating material for a thermal battery, a preparation method thereof, and a thermal battery prepared therefrom. Background Art

[0002] Thermal battery, also known as heat-activated reserve battery, is a primary battery that uses the battery's own heating system to heat the non-conductive solid salt electrolyte at room temperature to a molten ion state to work. It is widely used in weapon systems such as torpedoes and missiles due to its many advantages such as short activation time, high power density, long storage time, and wide operating temperature range.

[0003] As a power source for national defense equipment, the technological development of thermal batteries will directly affect the combat performance of weapon systems. In order to meet the electrical energy needs of weapon systems with different strike purposes in modern warfare, the performance indicators of thermal batteries, such as activation time and load capacity, are increasingly required. The main factors affecting the activation time of thermal batteries include the burning rate of the heating agent and the heat transfer rate inside the battery stack, while the load capacity is mainly related to the conductivity of the electrode material. At present, conventional thermal battery heating materials are mainly zirconium powder heating agents and iron powder heating agents. Among them, zirconium powder heating agents have a fast burning rate, but the gas production after combustion is large, and the conductivity of the combustion products is extremely poor, which significantly affects the battery's load capacity. Iron powder heating agents produce less gas when burned, and the conductivity of the products is adjustable, but their own burning rate is slow, which limits the battery activation time. Therefore, it is an important direction for the development of thermal batteries to develop new fast burning rate heating materials with both fast burning rate and high conductivity, and further improve the technical level of thermal batteries. Summary of the invention

[0004] The object of the present invention is to provide a fast burning rate heating material for a thermal battery, a preparation method thereof and a thermal battery prepared therefrom. The heating material adopts a bimetallic nano energetic film material with fast burning rate and high reaction activity, which can effectively improve the battery response speed and shorten the activation time.

[0005] To achieve the above objectives, the present invention discloses a fast-burning and fast-heating bimetallic nano energetic film material for thermal batteries, which is formed by alternately stacking two metal foils together, wherein one metal is Al and the other is one of Ni, Ti, Nb, and Cu. The thickness of the bimetallic nano energetic film material is 0.1 mm to 0.5 mm.

[0006] A preparation method of a fast-burning and fast-heating bimetallic nano energetic film material for a thermal battery comprises the following steps: using Al foil, Ni foil, Ti foil, Nb foil and Cu foil metal foils of fixed thickness as initial raw materials, selecting Al foil and another metal foil for annealing in a tubular furnace, and introducing a protective atmosphere into the tubular furnace; cutting the annealed metal foil into square pieces of suitable size, and then ultrasonically cleaning the square metal foil pieces; alternately stacking the two cleaned and dried metal foils together and placing them in a vacuum hot press for hot pressing; and then using a precision rolling mill to perform multiple cumulative lamination rolling on the hot-pressed material to obtain the bimetallic nano energetic film material.

[0007] Preferably, the metal foil has a thickness of 30 μm to 200 μm.

[0008] Preferably, the annealing temperature is 600° C. to 750° C., and the annealing time is 1.5 h to 3.5 h.

[0009] Preferably, the protective atmosphere is one of nitrogen or argon.

[0010] Preferably, the side length of the square metal foil is 5 mm to 15 mm.

[0011] Preferably, the cleaning agent is one of acetone, ethanol and deionized water.

[0012] Preferably, the thickness of the alternating stacking is 1 mm to 2 mm.

[0013] Preferably, the hot pressing temperature is 150° C. to 300° C., the pressure is 5 MPa to 20 MPa, and the hot pressing time is 1.5 h to 3.5 h.

[0014] Preferably, the rolling thickness is 0.1 mm to 0.5 mm, and the number of rolling passes is 15 to 25.

[0015] The present invention also provides a thermal battery, which comprises the fast-burning and fast-heating bimetallic nano energetic film material.

[0016] Beneficial effects of the present invention: Using bimetallic nano energetic thin film materials as thermal battery heating materials can effectively accelerate the heat transfer rate of thermal battery positive electrode materials in the initial activation stage and shorten the activation time. The material can be prepared by a hot pressing and rolling composite process. During the preparation process, it can be regulated by controlling synthesis parameters such as annealing temperature, reaction time, hot pressing temperature, hot pressing time and rolling times to prepare materials with different morphologies, different burning rates and different energy densities, which has a positive role in promoting the research of fast burning rate and high conductivity heating materials for thermal batteries. The preparation method of the bimetallic nano energetic thin film thermal battery heating material provided by the present invention is also applicable to the preparation of other multi-metal alloy films and multi-metal alloy thin film heating materials, which is of great significance to the exploration and application of new alloy thin film thermal battery heating materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Discharge performance curve of the fast burning and heating material in Example 1 of the present invention.

[0018] Figure 2 Discharge performance curve of iron powder heating agent in comparative example 1 of the present invention.

[0019] Figure 3 Comparison of activation time between Example 1 of the present invention and Comparative Example 1.

[0020] Figure 4 Comparison of battery internal resistance between Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0021] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0022] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0023] The fast-burning-rate heating bimetallic nano energetic film material for the thermal battery of the present invention is formed by alternately stacking two metal foils, wherein one metal is Al and the other is one of Ni, Ti, Nb, and Cu. The bimetallic nano energetic film material has a thickness of 0.1 mm to 0.5 mm.

[0024] A preparation method of a fast-burning and fast-heating bimetallic nano energetic film material for a thermal battery comprises the following steps: using Al foil, Ni foil, Ti foil, Nb foil and Cu foil metal foils of fixed thickness as initial raw materials, selecting Al foil and another metal foil for annealing in a tubular furnace, and introducing a protective atmosphere into the tubular furnace; cutting the annealed metal foil into square pieces of suitable size, and then ultrasonically cleaning the square metal foil pieces; alternately stacking the two cleaned and dried metal foils together and placing them in a vacuum hot press for hot pressing; and then using a precision rolling mill to perform multiple cumulative lamination rolling on the hot-pressed material to obtain the bimetallic nano energetic film material.

[0025] Furthermore, the annealing temperature is 600° C. to 750° C., and the annealing time is 1.5 h to 3.5 h.

[0026] Furthermore, the protective atmosphere is nitrogen or argon.

[0027] Furthermore, it is characterized in that the side length of the square metal foil is 5mm to 15mm.

[0028] Furthermore, the cleaning agent is one of acetone, ethanol and deionized water.

[0029] Furthermore, the thickness of the metal foil is 30 μm to 200 μm, and the thickness of the alternately stacked foil is 1 mm to 2 mm.

[0030] Furthermore, the hot pressing temperature is 150° C. to 300° C., the pressure is 5 MPa to 20 MPa, and the hot pressing time is 1.5 h to 3.5 h.

[0031] Furthermore, the rolling thickness is 0.1 mm to 0.5 mm, and the number of rolling passes is 15 to 25.

[0032] A thermal battery adopts the thermal battery fast burning rate heating bimetallic nano energetic film material or the thermal battery fast burning rate heating bimetallic nano energetic film material prepared by the preparation method.

[0033] The bimetallic nano energetic film material of the present invention is an energetic material and a new fast burning heating material for thermal batteries with great application prospects. The bimetallic nano energetic film material can undergo a violent exothermic reaction under relatively low energy stimulation, and has the characteristics of fast reaction speed, large heat release, no gas generation, and the reaction product is a metal alloy. Using it as a thermal battery heating material can effectively shorten the battery activation time and reduce the internal resistance during the operation of the thermal battery, thereby comprehensively improving the electrochemical performance of the thermal battery.

[0034] In the following embodiments of the present invention, the method for testing the electromechanical performance of the thermal battery prototype is as follows: first, the bimetallic nano energetic film is cut into discs. Then, at 2T / cm 2Under the pressure of , FeS2 cathode material powder and ternary all-lithium salt electrolyte powder (LiF-LiCl-LiBr) were pressed into single-layer sheets, and then stacked and placed into single cells in the order of heating sheet, cathode sheet, electrolyte sheet, cathode, and current collector. 15 groups of single cells were connected in series, pressurized and tightened, and then sealed into the battery housing to assemble into a thermal battery prototype. The assembled thermal battery prototype was discharged under constant current superimposed pulse load conditions.

[0035] Example 1

[0036] Place 35μm thick Al foil and 35μm thick Ni foil in a tubular furnace, fill with nitrogen, and anneal at 600℃ for 1.5h. Cut the annealed Al foil and Ni foil into square pieces with a side length of 5mm, and then place the metal foil in a beaker filled with acetone for ultrasonic treatment for 10min. Then, alternately stack the cleaned and dried Al foil and Ni foil to a thickness of about 1mm and place them in a vacuum hot press, and hot press them at 150℃ and 5MPa pressure for 1.5h. Finally, use a precision rolling mill to roll the hot-pressed material 15 times into a 0.1mm thick film to obtain the Al / Ni nano energetic film material.

[0037] Example 2

[0038] Place 50μm thick Al foil and 50μm thick Ti foil in a tubular furnace, fill with nitrogen, and anneal at 650℃ for 1.5h. Cut the annealed Al foil and Ni foil into square pieces with a side length of 5mm, and then place the metal foil in a beaker filled with acetone for ultrasonic treatment for 10min. Then, alternately stack the cleaned and dried Al foil and Ni foil to a thickness of about 1mm and place them in a vacuum hot press, and hot press them at 150℃ and 5MPa pressure for 1.5h. Finally, use a precision rolling mill to roll the hot-pressed material 15 times into a 0.2mm thick film to obtain the Al / Ti nano energetic film material.

[0039] Example 3

[0040] Place a 150μm thick Al foil and a 150μm thick Ni foil in a tubular furnace and fill it with nitrogen for annealing at 750℃ for 3.5h. Cut the annealed Al foil and Ni foil into square pieces with a side length of 15mm, and then place the metal foil in a beaker filled with deionized water for ultrasonic treatment for 10min. Then, alternately stack the cleaned and dried Al foil and Ni foil to a thickness of about 2mm and place them in a vacuum hot press, and hot press them at 350℃ and 5MPa pressure for 1.5h. Finally, use a precision rolling mill to roll the hot-pressed material 25 times into a 0.2mm thick film to obtain the Al / Ni nano energetic film material.

[0041] Example 4

[0042] Place 35μm thick Al foil and 100μm thick Cu foil in a tubular furnace, fill with nitrogen, and anneal at 650℃ for 2h. Cut the annealed Al foil and Ni foil into square pieces with a side length of 5mm, and then place the metal foil in a beaker filled with ethanol for ultrasonic treatment for 10min. Then, alternately stack the cleaned and dried Al foil and Ni foil to a thickness of about 1mm and place them in a vacuum hot press, and hot press them at 150℃ and 5MPa pressure for 1.5h. Finally, use a precision rolling mill to roll the hot-pressed material 18 times into a 0.1mm thick film to obtain the Al / Cu nano energetic film material.

[0043] Comparative Example 1

[0044] At 2T / cm 2 Under the pressure of , FeS2 cathode material powder, ternary all-lithium salt electrolyte powder (LiF-LiCl-LiBr) and iron powder heating agent were pressed into single-layer sheets, and then stacked and stacked into single cells in the order of heating sheet, cathode sheet, electrolyte sheet, cathode and current collector. 15 groups of single cells were connected in series and pressurized and tightened, and then sealed into the battery housing to assemble the thermal battery prototype. The assembled thermal battery prototype was discharged under constant current superimposed pulse load conditions.

[0045] like Figure 1-4 As shown in the figure, compared with the traditional iron powder heating agent, the thermal battery using Al / Ni nano energetic film material as the heating agent has a significantly faster activation speed and a lower internal resistance during the thermal battery discharge process. This shows that the use of nano energetic film material as the thermal battery heating material can effectively shorten the battery activation time, reduce the internal resistance during the operation of the thermal battery, and comprehensively improve the discharge performance of the thermal battery.

[0046] The embodiments described above are only used to illustrate the technical ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. The patent scope of the present invention cannot be limited only by these embodiments. That is, any equivalent changes or modifications made to the spirit disclosed by the present invention still fall within the patent scope of the present invention.

Claims

1. A fast burning rate heating bimetallic nano energetic film material for thermal battery, characterized in that: It is formed by alternately stacking two metal foils together, wherein one metal is Al and the other is one of Ni, Ti, Nb, and Cu. The thickness of the bimetallic nano energetic film material is 0.1 mm to 0.5 mm.

2. A method for preparing a fast burning heating bimetallic nano energetic film material for a thermal battery, characterized in that: Using Al foil, Ni foil, Ti foil, Nb foil and Cu foil of fixed thickness as initial raw materials, Al foil and another metal foil are selected for annealing in a tubular furnace, and a protective atmosphere is introduced into the tubular furnace; the annealed metal foil is cut into square pieces of suitable size, and then the square metal foil is ultrasonically cleaned; the two cleaned and dried metal foils are alternately stacked together and placed in a vacuum hot press for hot pressing; and the hot-pressed material is repeatedly accumulated and rolled using a precision rolling mill to obtain a bimetallic nano energetic film material.

3. The method for preparing the fast burning rate heating bimetallic nano energetic thin film material for thermal battery according to claim 2, characterized in that: The annealing temperature is 600°C to 750°C, and the annealing time is 1.5h to 3.5h.

4. The method for preparing the fast burning rate heating bimetallic nano energetic thin film material for thermal battery according to claim 2, characterized in that: The protective atmosphere is nitrogen or argon.

5. The method for preparing the fast burning rate heating bimetallic nano energetic thin film material for thermal battery according to claim 2, characterized in that: The side length of the square metal foil is 5mm to 15mm.

6. The method for preparing the fast burning rate heating bimetallic nano energetic thin film material for thermal battery according to claim 2, characterized in that: The cleaning agent is one of acetone, ethanol and deionized water.

7. The method for preparing the fast burning rate heating bimetallic nano energetic thin film material for thermal battery according to claim 2, characterized in that: The thickness of the metal foil is 30 μm to 200 μm, and the thickness of the alternately stacked foil is 1 mm to 2 mm.

8. The method for preparing the fast burning rate heating bimetallic nano energetic thin film material for thermal battery according to claim 2, characterized in that: The hot pressing temperature is 150° C. to 300° C., the pressure is 5 MPa to 20 MPa, and the hot pressing time is 1.5 h to 3.5 h.

9. The method for preparing the fast burning rate heating bimetallic nano energetic thin film material for thermal battery according to claim 2, characterized in that: The rolling thickness is 0.1 mm to 0.5 mm, and the number of rolling passes is 15 to 25.

10. A thermal battery, characterized in that: The fast burning rate heating bimetallic nano energetic film material for thermal battery is prepared by the fast burning rate heating bimetallic nano energetic film material for thermal battery as described in claim 1 or the preparation method as described in any one of claims 2-9.

Citation Information

Patent Citations

  • Reactive foil assembly

    CN101394997A

  • Preparation method of metallic / intermetallic compound laminar composite material

    CN105414219A

  • Preparation method of Ti-Al intermetallic compound laminated composite boards and mold thereof

    CN112439804A

  • Preparation method of large-size metal aluminide curved-surface thin-wall component

    CN113151701A

  • Composite reactive multilayer foil

    CN1817539A